Providing Several Skills to Treat Complex Infectious Stones of Solitary Kidney in a Patient Failed to Undergo Percutaneous Nephrolithotomy: A Case Report - Feng, Dechao; Wei, Wuran (Frontiers in Surgery, 2021)
Conservative treatment is closely associated with renal deterioration for patients with renal staghorn stones. It is well-recognized that percutaneous nephrolithotomy (PCNL) is recommended as the first-line treatment of renal stones larger than 2cm due to its higher stone clearance and cost-effectiveness when compared with other treatment alternatives, like shockwave lithotripsy and flexible ureteroscopy. Besides, our findings indicated that miniaturized PCNL could be served as an alternative to PCNL with a higher stone-free rate and a lower hemorrhage risk. Despite the higher cost-effectiveness of PCNL, the management of staghorn stones are still controversial in some special situations, such as solitary kidney. Herein, we present a case with complex infectious stones of right-sided solitary kidney, complaining of persistent pain in the right waist. The rarity of this case is that it is difficult to encounter this cotton-like staghorn stones clinically which are resistant to holmium laser lithotripsy, and the particularity is that this is a patient with solitary kidney failing to undergo PCNL. We found that the combination of intermittently high-frequency oscillation and flexible ureteroscopy forceps might contribute to treat complex infectious stones in a patient with solitary kidney. Our surgical experience might be beneficial to such patients undergoing flexible ureteroscopy in clinical practice.